PENGARUH E-SERVQUAL TERHADAP CUSTOMER SATISFACTION, TRUST, DAN REPEAT USAGE - Chandra, Ade Santoso; Rahyuda, Ketut; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.06.TAHUN 2015, 2015)
Electronic banking (e-banking) is now becoming increasingly popular in Indonesia. E-SERVQUAL designed to measure the gap between expectations and perceptions of the electronic services provided. This study aims to investigate empirically the influence of E-SERVQUAL, customer satisfaction, trust and repeat usage of e-banking. Approach the survey method used in this study to examine the dimensions of E-SERVQUAL perceived by 180 respondents. The samples using purposive sampling method. Hypotheses were tested using SEM with the help of computer software AMOS 18. Based on the results of testing the E-SERVQUAL found positive and significant effect on customer satisfaction, E-SERVQUAL positive and significant effect on the trust, E-SERVQUAL positive and significant effect on repeat usage, customer satisfaction positive and significant effect on trust, customer satisfaction positive and significant effect on repeat usage, and trust positive and significant effect on repeat usage.
Keywords: e-servqual, customer satisfaction, trust, repeat usage